Muslim minority in China: a case of Uyghur Muslims in Xinjiang - Fathil, Fauziah (Springer, 2019)
In recent years, the Uyghurs in Xinjiang-Uyghur Autonomous Region (XUAR) have increasingly been viewed disapprovingly by the Chinese government. This followed a series of unwanted incidents that broke out in Xinjiang, especially from the 1990s onwards. Consequently, the Uyghurs who are a minority group of Turkic origin have been subjected to some repressive measures aimed to undermine their Turkic-Uyghur and Islamic identities such as the prohibition on the wearing of veils or burqas, growing beard by young men, as well as restriction on performing prayers in mosques, fasting during Ramadhan, etc. Additionally, mass internment camps were set up for indoctrination purposes. While the Beijing government argued that the measures are necessary in order to curb possible threats to Chinese national security posed by some Uyghur nationalist and separatist groups, the latter viewed the oppressive policy as an unjustified ethnic discrimination against the Uyghurs primarily due to their Turkic–Uyghur–Islamic identity that does not blend well with the dominant Chinese or Han culture. Using mainly content analysis and library research approach, the paper sheds light on the brief history of Xinjiang and the Uyghur community, as well as their socio-economic and political conditions under the Chinese rule. The contemporary situation in Xinjiang including the tenacious issue of Uyghur nationalism and separatism form the central discussion of the paper followed by the countermeasures of the Chinese government to overcome the problems, some of which are repressive, and finally, the reactions of the Uyghurs towards those measures.